Simulasi Pengisian Kapasitor Berulang Menggunakan Metode Numerik SCILAB - Jumriah; Husnia Musda Mulia; Winarsi (Applied Physics of Cokroaminoto Palopo, 2021)
For the problem that will be discussed in this article, which is about how to charge capacitors repeatedly using a numerical method using the Scilab application. Scilab is a software for numerical computing that is open source and can be run on Linux, Windows and Marcos operating systems